(untitled) (International Journal of Engineering and Computer Science, 2017)
In today’s digital world, in every field there is massive use of digital contents. Digital documents can be copied and scattered easily to large numbers of people without any cost. People can download audio, image and video files, and they can share them with friends and they can influence or change their original contents. Due to this, there is more probability of copying of such digital information. So, there is an urgent need of prohibiting such illegitimate copyright of digital media. Digital watermarking (DWM) is the dominant solution to this problem. This paper aims to provide an exhaustive survey of digital watermarking techniques especially focuses on image watermarking types and its applications in today’s world.